Acute arthritis of the right temporomandibular joint due to Lyme disease: a case report and literature review - Christina Weise; Matthias C. Schulz; Karin Frank; Marcel Cetindis; Bernd Koos; Hannes Weise (BMC, 2021)
Abstract Background Lyme disease is the most frequent tick-borne infectious disease in Europe. It often presents with a wide variety of symptoms. For this reason, affection of the temporomandibular joint (TMJ) caused by Lyme disease (LD) can be misdiagnosed as a common temporomandibular disorder (TMD). Case presentation The purpose of this case report of a 25-year-old woman presenting to the Departments of Orthodontics and Oral and Maxillofacial Surgery with extensive symptoms of temporomandibular disorder is to illustrate the delayed diagnosis of Lyme disease which was only made after extensive therapy of the temporomandibular joint. The specialist literature only reports a few cases of patients suffering from Lyme disease with TMJ manifestations. Conclusion This case report and the relevant literature review aim to emphasize the importance of accurate request of medical history and differential diagnosis of acute TMJ arthritis and arthralgia. Early interdisciplinary diagnosis of Lyme disease and early antibiotic therapy are essential to avoid misdiagnosis and unnecessary, sometimes invasive, therapies.